Intangible Aspects Attached to the Mahākāla Worship in Hindu and Buddhist Text - Rana, Poonam R.L. (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Mahākāla is the God of Time, Maya, Creation, Destruction and Power. He is a form of a Brahman Mahākāla that is affiliated with Lord Shiva. His abode is the cremation grounds. He has four arms and three eyes, and is often depicted to be sitting on five corpses. In his arms he wields a trident, drum, sword and hammer. He rubs ashes, from the cremation ground, on himself. He is surrounded by vultures and jackals. His consort is Kāli. Mahākāla and Kāli are the personification of time and destruction.